Mobilitätsprozesse in Südostliberia - Schulze, Willi (ERDKUNDE, 1976)
The investigation of migrations to the Greenville and Cavalla Plantations reveals several spatial and temporal variations in the patterns of migrations among the three tribes concerned, namely the Grebo, Krahn and Kru. The variations observed in the source regions as in those of destination are to be attributed to managerial, economic, transport-geographical and other causes. They have had the effect of an irregular labour exodus from the tribal areas, which renders regional planning difficult in a sparsely populated area, and prevents an even development. Apart from longer-term migrations there are processes of short-term mobility as well. Besides the friends and relatives effect the acquisition of innovative consumer goods not in everyday, superior demand, is of especial interest for social geography since it manifests not only the advance of items and demands of modern civilization into a still largely traditionally-oriented, agrarian plantation society, but on the other hand also creates new material and non-material wishes,demands and changes in the cultural sphere.